(untitled) (Research, Society and Development, 2021)
This article discusses how networking is constituted in the dehospitalization process. It usually involves users with some condition of dependence due to chronic issues that are evident when associated with social expressions. The study methodology was based on qualitative nature, in which participant observation was used together with semi-structured interviews with the dehospitalization sector of a public hospital located in the city of Rio de Janeiro. The findings show that the networking encompasses both internal and external articulations, having as its main challenges the precariousness of public policies, the personal relations and the difficulties of communication among teams. We conclude that there is a need to think about dehospitalization from the perspective of public policies and that ensure care as a right.